The Practical Use Of Resistance Modeling To Interpret The Gas Separation Properties Of Hollow Fiber Membranes - Ismail, A. F.; Shilton, S. J. (Penerbit UTM Press, 2000)
A simple resistance modeling methodology is presented for gas transport through asymmetric polymeric membranes. The methodology allows fine structural properties such as active layer thickness and surface porosity, to be determined from experimental gas permeation data. This paper, which could be regarded as a practical guide, shows that resistance modeling, if accompanied by realistic working assumptions, need not be difficult and can provide a valuable insight into the relationships between the membrane fabrication conditions and performance of gas separation membranes.